Animal movement drives variation in seed dispersal distance in a plant–animal network. Issue 1894 (16th January 2019) - Rehm, E.; Fricke, E.; Bender, J.; Savidge, J.; Rogers, H.
Abstract : Frugivores play differing roles in shaping dispersal patterns yet seed dispersal distance is rarely quantified across entire communities. We model seed dispersal distance using gut passage times and bird movement for the majority (39 interactions) of known bird–tree interactions on the island of Saipan to highlight differences in seed dispersal distances provided by the five avian frugivores. One bird species was found to be a seed predator rather than a disperser. The remaining four avian species dispersed seeds but differences in seed dispersal distance were largely driven by interspecific variation in bird movement rather than intraspecific variation in gut passage times. The median dispersal distance was at least 56 m for all species-specific combinations, indicating all species play a role in reducing high seed mortality under the parent tree. However, one species—the Micronesian Starling—performed 94% of dispersal events greater than 500 m, suggesting this species could be a key driver of long-distance dispersal services (e.g. linking populations, colonizing new areas). Assessing variation in dispersal patterns across this network highlights key sources of variation in seed dispersal distances and suggests which empirical approaches are sufficient for modelling how seed dispersal mutualisms affect populations and communities.